Efficacy of tamsulosin therapy in females with non-neurogenic lower urinary tract symptoms - Ahmad, Tariq; Rahman, Ata ur; Khan, Muhammad Amjad (Journal of Postgraduate Medical Institute, 2014)
Objective: To determine the efficacy of tamsulosin therapy for the treatment of lower urinary tract symptoms (LUTS) in women. Methodology: This study was conducted in Institute of kidney diseases, Hayatabad medical complex Peshawar from April 2011 to September 2012. All female patients aged 13 and above with LUTS were included. After taking history, physical examination and baseline investigations, specific investigations such as urine culture, urodynamics and ultrasound with postvoid residual volume were performed. Base line international prostate symptom score (IPSS), maximal flow rate (Qmax) and post-void residual volume (PVR) were recorded for each patient before starting treatment. Tamsulosin therapy was initiated at 0.4 mg once daily and continued for 6 weeks. In follow up visits after 6 weeks, IPSS, Qmax, and PVR were repeated for evaluation of outcomes. Results: Out of 94 patients, 10 did not come for follow up. Mean age of the sample was 43 years. Presenting complaints were increased frequency (n=67, 79.8%), Urgency (n=62, 73.8%), Nocturia (n=64, 54.8%), Feeling of incomplete bladder emptying (n=17, 20.2%), Poor stream (n=15, 17.9%), Hesitancy (n=5, 6.0%), and Intermittency (n=2, 2.4%). Mean PVR and IPPS decreased and Qmax improved significantly with p value <0.01. Efficacy was 90.5%. It was 52(96.3%) in pre-menopausal and 24(80.0%) in postmenopausal women. Only Two patients experienced drowsiness. Conclusion: Tamsulosin significantly decrease IPSS, PVR and improve Qmax, so they should be used as first line treatment for moderate to severe LUTS in women.